ИСПОЛЬЗОВАНИЕ ПРОЕКТНОГО ПОДХОДА ОРГАНАМИ ГОСУДАРСТВЕННОЙ ВЛАСТИ В ЦЕЛЯХ СТИМУЛИРОВАНИЯ ИННОВАЦИОННОЙ ДЕЯТЕЛЬНОСТИ - E. Asaulenko; A. Struk (Вестник университета, 2016)
The article deals with basic aspects, mechanisms and tools the project approach used by public authorities to stimulate innovation in organizations using the financial resources of state development institutions. The article focuses on the use and improvement of improving the design to ensure maximum effect from the use of innovative product or service.